Investment Opportunity Set (Ios): Between Opportunities and Threats for Pharmaceutical Companies in Indonesia - Nurlatifah, Siti (Journal Markcount Finance, 2024)
Investment Opportunity Set (IOS) is the opportunity that a company has to make investments that can increase the value of the company. IOS can be influenced by various factors, one of which is the financial performance of the company. This study aims to examine the effect of financial performance on IOS in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the period of 2015-2020. Financial performance is measured by using profitability ratio, solvency ratio, and activity ratio, while IOS is measured by using Market Book Value to Equity (MBVE). This study uses quantitative data in the form of annual financial statements and stock prices of pharmaceutical companies obtained from the official website of IDX. The sampling technique uses purposive sampling with certain criteria, resulting in 54 data samples. The data analysis technique uses multiple linear regression analysis with SPSS for Windows version 26.0 program. The results show that financial performance simultaneously has a significant effect on IOS with F value of 18.859 and significance value of 0.000. Partially, profitability ratio has a positive and significant effect on IOS, solvency ratio has a negative and significant effect on IOS and activity ratio has a positive and significant effect on IOS. This study implies that pharmaceutical companies can increase IOS by improving financial performance, especially profitability ratio and activity ratio, and reducing solvency ratio.